Assessment of the calcification of the nuchal ligament and osteophytes of the cervical spine in obstructive sleep apnoea subjects and snorers. (3rd October 2015) - Ando, E.; Shigeta, Y.; Nejima, J.; Yamanaka, H.; Hirai, S.; Ogawa, T.; Clark, G. T.; Enciso, R.
Summary: The previous reports suggest that obstructive sleep apnoea (OSA) is related to metabolic syndrome, mineral metabolism disorders and cardiovascular disease. In addition, a possible relationship between obesity and the calcification of ligaments has been implied. However, the potential link between OSA and the calcification of ligaments has not been directly studied. In this present study, to investigate the potential link between OSA and the calcification of ligaments, we examined the prevalence of the calcification of ligaments in OSA patients and the relationship between these findings and OSA severity. Eighty consecutive patients (60 males, 20 females) diagnosed as OSA or a heavy snorer based on full‐night polyso‐mnography were retrospectively recruited from May 2006 to July 2008. Each patient underwent cephalometric imaging examination before the arrangement of an oral appliance. One calibrated observer (YS) reviewed the cephalometric images for the presence of calcification of the nuchal ligament and osteophytes of the cervical spine. The prevalence of calcification of the nuchal ligament in OSA patients and snorers was 46·3% (males: 52%, females: 30%) There was a significant positive correlation between the severity of OSA (AHI) and the calcification of the nuchal ligament before and after adjusting for BMI. The prevalence of the calcification of the nuchal ligament in OSA subjects and snorers was higher than in previous studies with non‐OSA subjects. In addition, it is suggested that the severity of OSA correlates with the presence of calcification of the nuchal ligament.